Digital Media Integration in Islamic Religious Education: Students' Responses and Islamic Value Formation - Viki Bayu Mahendra; Rochmawati Sholikhah Sukemi; Ashabil Yaqin; Ghufron Ali Sya'bana (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The growing adoption of digital technology has transformed instructional practices in Islamic Religious Education (IRE), creating opportunities to improve learning quality while preserving the ethical and spiritual objectives of Islamic education. This study investigates students' responses to the integration of digital media in IRE and examines its relationship with Islamic value formation at SMA Al-Azhar Syifa Budi Surakarta, Indonesia. A descriptive quantitative survey was conducted involving 82 students who had experienced digitally supported IRE instruction. Data were collected through a validated 15-item questionnaire covering three dimensions: digital media integration, contemporary Islamic education, and students' learning responses. Descriptive statistical techniques, including frequencies, percentages, and mean scores, were employed to analyze the data. The findings indicate that students expressed highly positive perceptions of digital media integration, with an overall mean score of 4.25 (85.01%), classified as very good. The strongest evaluation emerged in the dimension of Islamic value formation, suggesting that technology-supported learning can reinforce religious understanding, ethical awareness, and responsible technology use when guided by appropriate pedagogical practices. Nevertheless, students' concentration received comparatively lower ratings, indicating the need for more structured and interactive digital learning activities. These findings highlight that effective digital integration in IRE depends not only on technological resources but also on pedagogical design capable of balancing instructional innovation with the cultivation of Islamic values.